The Effect of Carbon Nanotubes on the Viscosity and Surface Tension of Heat Transfer Fluids—A Review Paper - Ibrahim Khoswan; Abdelrahim Abusafa; Saad Odeh (Energies, 2024)
The connection between surface tension and viscosity has been the subject of several pieces of research on nanofluids. Researchers have discovered differing relationships between these two suspension qualities in the literature. Surface tension and viscosity have been found to be correlated in certain research works but not in other. The behavior of these fluids may be influenced by several factors, including temperature, the presence of surfactants, and the functional groups on carbon nanotubes (CNTs). This study investigates the relationship between surface tension and viscosity in CNT-Nanofluids by reviewing earlier research on the impact of CNT addition on water’s intermolecular interactions. The findings show that depending on different aspects of the nanofluids, the connection is complicated and uncertain. The study shows that although temperature and the addition of carbon nanotubes affect both surface tension and viscosity, other studies only consider how these factors affect one of these qualities. We conclude that under certain heat transfer circumstances, there is no clear-cut relationship between surface tension and viscosity in CNT–water fluids.